Transforming defence in Ghana's Fourth Republic - Salihu, Naila (Cranfield University, 2018)
Armed forces play an instrumental role in maintaining stability in West Africa, yet they have also been a major destabilizing actor due to their role in frequent coup d’etats and human rights abuse. Ghana’s armed forces in particular, has a colonial and authoritarian history. It therefore requires change to align with the political transition of the country. The thesis seeks to answers to the question; has Ghana’ process of defence transformation contributed to healthier civil-military relations and consolidation of democracy in the Fourth Republic? David Chuter’s Guide to Defence Transformation and Rebecca Schiff’s Concordance Theory of civil-military relations provide a dual framework of analyses of developmensa in Ghana’s defence sector since 1992. A qualitative approach to research design, data gathering and analysis was used to establish that Ghana’s defence sector has undergone transformational chance which has been organically driven by the political, social-economic and security conditions of the country. Ghana Armed Forces in particular, has gradually undergone cultural, human, organizational and political transformation. These relative changes have contributed to a politico-military concordance that has helped sustain the Fourth Republic. Successes or otherwise of the reforms are very much dependent on commitment to change by both political authorities and the military hierarchy. There is agreement between military and political elites on key variables; social composition of the officer corps, recruitment, political decision-makiing process and military style. There have been some changes where the state and its security and defence institutions are no longer seen as agents of fear and repression. Nonetheless, the citizenry are not factored into the defence decision-making process. The opening up of the political space has provided opportunities for civil society actors and media to begin to show interest in engaging the military. Ghana has made satisfactory progress in bringing the defence sector in time with the current democratic dispensation. Yet, there is the need for the Ghana to do more by initiating more holistic defence transformation process to effectively transform the armed forces and other defence management and oversight institutions.